Dynamic Photoswitching of Electron Energy Levels at Hybrid ZnO/Organic Photochromic Molecule Junctions. (30th May 2018) - Wang, Qiankun; Ligorio, Giovanni; Diez‐Cabanes, Valentin; Cornil, David; Kobin, Björn; Hildebrandt, Jana; Nardi, Marco Vittorio; Timpel, Melanie; Hecht, Stefan; Cornil, Jérôme; List‐Kratochvil, Emil J. W.; Koch, Norbert
Abstract: The functionality of interfaces in hybrid inorganic/organic (opto)electronic devices is determined by the alignment of the respective frontier energy levels at both sides of the heterojunctions. Controlling the interface electronic landscape is a key element for achieving favourable level alignment for energy and charge transfer processes. Here, it is shown that the electronic properties of polar ZnO surfaces can be reversibly modified using organic photochromic switches. By employing a range of surface characterization techniques combined with density functional theory calculations, it is demonstrated that self‐assembled monolayers (SAMs) of photochromic phosphonic acid diarylethenes (PA‐DAEs) can be employed to reversibly change the electronic properties of polar ZnO/SAM structures by light stimuli. The highest occupied molecular orbital level of PA‐DAE is raised by 0.7 eV and the lowest unoccupied one lowered by 0.9 eV, respectively, upon illumination by ultraviolet light and the levels shift back to their original position upon illumination by green light. The results thus provide a pathway to tailor hybrid interface electronic properties in a dynamic manner upon simple light illumination, which can be exploited to reversibly tune the electrical properties of photoswitchable (opto)electronic devices. Abstract : Reversible changes in the energy level alignment of the frontier orbitals of photochromic phosphonic acid diarylethenes self‐assembled monolayers on polar ZnO faces are observed upon illumination with UV and green light. The findings provide a pathway in controlling the charge injection properties in photoswitchable devices dynamically through a simple light stimulus.